POSISI PENDIDIKAN ISLAM DALAM ISSU DEMOKRATISASI PENDIDIKAN NASIONAL - Irwan Saleh Dalimunthe (STIT Al-Ittihadiyah Labuhanbatu Utara, 2018)
Nation is being growing like Indonesia enough dynamic and beyond question blocked by various problems. One of between it was since the year 1998, Indonesia has done commitment jama'i to migrate life of nation from autoritary leadership towards democratic nature and bases on enableness of public with a hope is realized by it residence area having freedom of berkreasi by respecting social justice principle in framing state having philosophy Five Principles and UUD 1945. One of fundamental core which must get attention from thinker, observer, practitioner and stakeholder education to invitors Sistem Pendidikan Nasional is that any form, type, the line and education ladder in this state has the same rights and position. Including intitusi education in The Ministry of Religious affairs follows and bows in the order, with all consequences in its the applying. Its the implementation is public? people obliged to return to applies its (the partisifasi rights in developing quality of education, so that education returns to one with public as in early days growing of in Indonesia, as Ki Hajar Dewantara with its the Taman Siswa, modern Islamic sckool model of Ahmad Dahlan which always is continued Muhammadiyah, and Hasyim Asy'ari with Pesantren Salafiyah is growing mushroom below under upbringing of the Kiyai NU, and various other education institute types.